Hypoxia reduces the osteogenic differentiation of peripheral blood mesenchymal stem cells by upregulating Notch-1 expression. (2nd November 2019) - Yang, Minsheng; Liu, Haixin; Wang, Yihan; Wu, Guofeng; Qiu, Sujun; Liu, Chun; Tan, Zhiwen; Guo, Jiasong; Zhu, Lixin
ABSTRACT: Purpose : Mesenchymal stem cells (MSCs) seeded on biocompatible scaffolds have therapeutic potential for bone defect repair. However, MSCs can be affected by hypoxia and nutritional deficiency due to a lack of blood vessels in the scaffolds. Here, we explored the effects of hypoxia on MSC differentiation to clarify these mechanisms. Methods : Peripheral blood mesenchymal stem cells (PBMSCs) were cultured in small individual chambers with oxygen concentrations of 1%, 9%, and 21%. Cell proliferation was evaluated by Cell Counting Kit 8 assays, and cell survival was determined using live/dead assays. Scratch assays were performed to evaluate cell migration. Ca 2+ deposition/mineralization experiments, reverse transcription quantitative real-time polymerase chain reaction, and Western blotting were performed to assess the osteogenic differentiation of cells. Notch1 expression was downregulated by lentivirus-transfected PBMSCs to observe the effects of Notch1 knockdown on osteogenic gene and protein expression. Results : PBMSCs exposed to hypoxia (1% O2 ) demonstrated accelerated proliferation, increased migration, and reduced survival in the absence of serum. Although 9% oxygen promoted osteogenic differentiation, the osteogenic differentiation of PBMSCs was significantly reduced by 1% O2, and this effect was associated with increased Notch1 expression. Reducing Notch1 expression using small interfering RNA significantly restored the osteogenic differentiation of PBMSCs. Conclusions : Hypoxia accelerated proliferation, increased migration, and reduced PBMSC differentiation into osteoblasts by increasing Notch1 expression. These findings may contribute to the development of appropriate cell culture or in vivo transplantation conditions to maintain the full osteogenic potential of PBMSCs.